Comparative Study of Superselective Intra-Arterial Chemoradiotherapy versus Radical Surgery on Distant Metastasis for Advanced Oral Cancer. (14th April 2014) - Kobayashi, Wataru; Teh, Beng Gwan; Narita, Norihiko; Ito, Ryohei; Saito, Yuki; Furudate, Ken; Kimura, Hiroto; Kakehata, Sinya; Kawaguchi, Hideo
Abstract : Background . Distant metastasis is considerably more frequent in superselective intra-arterial chemoradiotherapy than other radical treatments for advanced oral cancers. However, there is no evidence supporting such claim. The purpose of this study was to report our experience in superselective intra-arterial chemoradiotherapy and conventional surgical management with particular focus on distant metastasis. Methods . One hundred seventy-two patients with oral squamous cell carcinoma in stages III and IV were included in this study. Retrospective analysis for DM rates and background between surgical management and superselective intra-arterial chemoradiotherapy was performed. Results . Distant metastasis developed clinically was detected in 24 out of 141 patients (17.0%) treated surgically and in 6 out of 31 patients (19.4%) treated with superselective intra-arterial chemoradiotherapy. There was no significant difference in the rate of distant metastasis between the 2 groups. Comparison of patients in both groups with and without distant metastasis revealed no differences in age, T classification, N classification, and treatment effect. Neck recurrence was the only significant risk factor for distant metastasis. Conclusion . No significant difference was found in the rate of distant metastasis between patients treated with surgical treatment and superselective intra-arterial chemoradiotherapy, and additional effort is needed to reduce the risk of distant metastasis.